2016
DOI: 10.1007/s00464-016-4988-5
|View full text |Cite
|
Sign up to set email alerts
|

Project 6 Summit: SAGES telementoring initiative

Abstract: Telementoring activities are poised for exponential growth but will require a coordinated effort by stakeholders working through and around a healthcare system not yet suited for this paradigm shift.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 3 publications
1
65
0
Order By: Relevance
“…With regard to the regulation of individual state medical licensing boards, currently telementoring can only be performed between a mentor and mentee who have medical licenses in that particular state. There are only two states (Delaware and West Virginia) that recognize licensed medical practitioners from outside of their own states and allow telementoring across state lines [10]. This regulatory limitation poses an issue whenever the only available mentor is licensed in a different state than the mentee's location where the telementoring is to be performed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With regard to the regulation of individual state medical licensing boards, currently telementoring can only be performed between a mentor and mentee who have medical licenses in that particular state. There are only two states (Delaware and West Virginia) that recognize licensed medical practitioners from outside of their own states and allow telementoring across state lines [10]. This regulatory limitation poses an issue whenever the only available mentor is licensed in a different state than the mentee's location where the telementoring is to be performed.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the constraints of individual state medical licensure requirements, the mentors and mentees were paired to be from the same states. There were two state exceptions (Delaware and West Virginia) that permit telementoring across state lines by a medical provider if invited by a physician from these two states [10]. In this initiative, telementoring was also performed internationally, specifically to Guatemala and Argentina.…”
Section: Logistics Of Telementoringmentioning
confidence: 99%
See 1 more Smart Citation
“…Our own tele-mentoring approach uses a similar continuing professional development design to extend LQMS knowledge and skills using trained quality assurance mentors as a central hub. Similar to accepted tele-mentoring methods in clinical medicine [15], our mentors built on an established working relationship with laboratory personnel, aided by regular video and telecommunication technologies, and the mentored participants were selected as capable quality assurance personnel to participate in an established educational framework that prepares them for the experience.…”
Section: Remote Tele-mentoringmentioning
confidence: 99%
“…The application of telemedicine should be guided by the same ethical principles upon which medi-providing this service(10) with surgical robots and joint development projects have appeared in recent years (11). Several review studies on the application of telementoring in mini-invasive surgery have been published, and concluded that it is a safe and effective procedure that is comparable to face-to-face mentoring (12)(13)(14)(15)(16)(17).…”
Section: Telemedicine Ethics and Ethical Guidelinesmentioning
confidence: 99%